2002
DOI: 10.1046/j.1365-2168.2002.02086.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of a randomized clinical trial of haemodilution with cell salvage in aortic surgery

Abstract: Autologous transfusion is cost neutral in aortic surgery even when surgical activity is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Although the cost-benefit ratio of ICS in this study was not directly assessed, economic analysis of ICS has been undertaken by other groups who found that even in centres with low levels of surgical activity, ICS is cost neutral [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Although the cost-benefit ratio of ICS in this study was not directly assessed, economic analysis of ICS has been undertaken by other groups who found that even in centres with low levels of surgical activity, ICS is cost neutral [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The value of this combination has been evaluated in a randomized controlled trial, confirming a significant reduction in allogeneic blood requirements [44]. This transfusion strategy combining ANH and ICS for AAA surgery was also cost-effective [41].…”
Section: Autologous Transfusionmentioning
confidence: 99%
“…Oxygen delivery following allogeneic blood is also impaired by loss of 2,3-diphosphoglycerate (2,3-DPG). Such effects may enhance the susceptibility to peri-operative infection in the elderly and worsen the outcome in aortic surgery [40,41]. More recently, the discovery of variant Creutzfeldt-Jakob disease prompted changes in the management of blood products, including the ban of British plasma from fractionation and routine leucodepletion of red cells.…”
Section: Blood Transfusion Strategiesmentioning
confidence: 99%
“…Not surprisingly, operator error can lead to significant problems, 14 thus underlining the need for appropriate training and standardized operating procedures. Haynes and colleagues 12 found that even when apparently different initial outlay or running costs were analyzed in annual or true cost per case basis, the calculated costs of three suppliers became very similar. They looked at initial capital costs, maintenance and cost of consumables.…”
mentioning
confidence: 99%
“…12 This study was actually in the context of aortic surgery so may not be strictly comparable to cardiac surgery, however the methodology could be applied to the cardiac context. Taking all factors into account, including capital and revenue, running costs and impact on procedure time compared to allogeneic RBCs the study found very little cost difference between CS and allogeneic transfusions.…”
mentioning
confidence: 99%